Respuesta :

Answer:

It is possible to find ​f(x+4) by replacing each occurrence of​ x by (x+4).

[tex]f(x+4) = x^2 +2x -3[/tex]

Step-by-step explanation:

We are given the following function in the question:

[tex]f(x) = x^2-6x+5[/tex]

We have to find the value of f(x+4).

It is possible to find ​f(x+4) by replacing each occurrence of​ x by (x+4).

This can be done in the following manner:

[tex]f(x) = x^2-6x+5\\f(x+4) =(x+4)^2 - 6(x+4) + 5\\f(x+4) = x^2 + 16 + 8x - 6x - 24 +5\\f(x+4) = x^2 +2x -3[/tex]

ACCESS MORE